A novel binder prepared from municipal solid waste incineration fly ash and phosphogypsum. (15th July 2023) - Wang, Shuai; Xue, Caihong; Zhao, Qingxin; Bai, Yanying; Guo, Weichao; Shi, Yuxuan; Qiu, Yongxiang; Pan, Huimin
Abstract: At present, the recycling technology for municipal solid waste incineration fly ash (MSWIFA) and phosphogypsum (PG) is not yet mature, and they are mostly disposed of in open piles or in situ landfills, taking up a lot of land resources and harmful to the environment. A novel binder was developed from MSWIFA and PG in this study. Firstly, the feasibility of using MSWIFA to activate slag (GGBS) and fly ash (FA) for a ternary binder MGF was investigated. Subsequently, based on the optimal mix proportions of MGF, 5%–15% PG was used to substitute GGBS for a quaternary binder MGFP. The results revealed that without PG, the alkali environment provided by MSWIFA can effectively activate GGBS and FA, achieving a compressive strength of 14.0 MPa at 3 d and 25.7 MPa at 28 d when MSWIFA: GGBS: FA = 3: 6: 1. The strength of the ternary binder MGF was further improved by the addition of 5% PG due to the fact that the SO4 2− from PG reacts with the intermediate product [Al(OH)6 ] 3- generated during MSWIFA activation of GGBS-FA to form ettringite which optimizes the microstructure of the hardened matrix. However, excessive PG over 5% was found to cause reduction in compressive strength, attributed to the dilution of the hydration products and the formation of cracks induced by excessive ettringite. The developed binders presented excellent ability in stabilization and solidification of heavy metals and the heavy metal leaching results meet the Chinese Standard GB18598-2019. The results obtained in this study provide technical support for the application of MSWIFA and PG in construction and building materials. Highlights: MSWIFA was used as alkali activator to prepare MGF/MGFP binder. PG can reduce porosity and improve compressive strength. Macroscopic properties and microscopic mechanism of MGF/MGFP were revealed. The leaching concentration of heavy metals in MGF/MGFP meets the Chinese standards.